PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN DI KELAS V SD UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Winda Sari Br Panjaitan; Safrida Napitupuluh; Nila Lestari; Abdul Mujib; Dalimawaty Kadir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Student Worksheets (LKPD) based on Problem Based Learning (PBL) in mathematics learning of fractions in grade V of Elementary School to improve student learning outcomes. This study uses the ADDIE development model consisting of five stages, but limited to the Development stage. The subjects of the study were grade V students of SD Negeri 006 Melayu Besar. Data collection was carried out through expert validation, teacher and student response questionnaires, and learning outcome tests. The validation results showed that the LKPD developed was in the